REFORMASI KEBIJAKAN FISKAL PROVINSI JAWA BARAT UNTUK PEMERATAAN EKONOMI DAN PEMBANGUNAN BERKELANJUTAN - Laksana, Satya (Creative Research Journal, 2024)
This study aims to elaborate and advocate for the Ecology-Based Provincial Budget Transfers (TAPE) mechanism as a policy instrument for managing environmental issues while reducing disparities in economic development. West Java faces pressing ecological challenges. It includes impacts of climate change, deforestation, water scarcity, land conversion, food security threats, and a significant socio-economic development gap between the North and the South. The Ecological Fiscal Transfer (EFT) has been applied in the National Government transfer mechanisms. The TAPE has been implemented in a few provinces of ”the Lungs of the World” as a derivative concept of EFT at the provincial government levels. This research examines experiences and best practices of TAPE implementation in other Provinces, then modifies the idea for the West Java context. It employs a Desk Study method, incorporating a literature review, policy analysis, interviews with stakeholders, and collecting regional government budgets of districts/municipalities. This study presents findings regarding the potential of TAPE to stimulate sustainable economic equity. This research provides comprehensive policy recommendations to address environmental problems and inter-regional fiscal capacity disparities in West Java. In detail, it promotes ecological performance indicators for formulating provincial financial aid allocations for regency/municipal governments and village governments.